If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -10) = 7 Reorder the terms: (-10 + x) = 7 Remove parenthesis around (-10 + x) -10 + x = 7 Solving -10 + x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + x = 7 + 10 Combine like terms: -10 + 10 = 0 0 + x = 7 + 10 x = 7 + 10 Combine like terms: 7 + 10 = 17 x = 17 Simplifying x = 17
| -5+7(x-2)=-35+5x | | 60-(x+2x-2)=0 | | 5x-2=22+3x | | 6-9+66=30 | | 3(x-2)(x-2)=27 | | 6p+6=2+2p | | 6v+21=-3(3-7v) | | 5x-2=5(x-1) | | (9x+6)+(3x)=90 | | 12x+1000= | | 5p-2-3p=16 | | 12x^2+4x+4=0 | | 3x+60-2=0 | | -6(x+8)-45=2-53 | | 19-12=x/8 | | 14=x+(x*.08) | | 4x-15+2x+3=48 | | -4x-15=19 | | 2(x-8)=8x+20 | | -5n=13-3 | | 5x-2=-8x+24 | | -16+3n=4n+7n | | 5x+6=2x+36 | | 4z+8x=360 | | 5x+6=2x+37 | | n-3+7=10+7n | | 10x-12+10x+32=180 | | -12x=15 | | 5k+5=-2-3k+k | | 7z=13-34 | | 5-2(x+3)=7 | | 9=72-13Z+2+M |